The Politics of the Nonviolent God: Reflections on René Girard and Karl Barth - Hunsinger, George (Scottish journal of theology, 1998)
Doctrines of the atonement in Christian theology, as Marlin E. Miller has pointed out, ‘usually limit their concern to reconciliation with God and, at most, consider reconciliation with others a secondary consequence of reconciliation with God’. Too often, in other words, the vertical aspect of reconciliation is allowed to overshadow its horizontal aspect. The vertical aspect of the atonement as it pertains directly to God is often treated in isolation as if its ethical implications were of no great importance. The reverse defect, however, would also appear to be widespread. Christian ethics as we know it today often seems to proceed as if the atoning work of Christ were of little or no relevance to its deliberations on human affairs. The social or horizontal aspect of reconciliation thereby eclipses its vertical aspect. Yet if the cross of Christ is indeed the very center of the center of the Christian gospel, as the church has historically believed, then how can it fail to determine the substance of Christian ethics as well as that of Christian theology? Moreover, how can the centrality of the cross fail to orient them both in any attempt to specify their inner unity, order and differentiation?